Contribution to the Empirics of Electricity Blackouts and Productivity in Nigeria - Kingsley, Imandojemu; Tonuchi, Joseph E. (Energy Economics Letters, 2021)
Purpose: The age-long problematic electricity situation and attendant loss of productive man-hour is forcing the resurgent proliferation of literature on the relationship between blackouts and productivity in developing countries. This study expands the scope of existing literature by pricing the cost of electricity blackout on productivity. Approach/Methodology/Design: The Fully Modified Ordinary Least Squares (FMOLS) that was developed by Phillips and Hansen (1990) was used to estimate the existing relationship. Data were sourced from the World Development Indicators, Energy Information Administration (EIA) website, the Central Bank of Nigeria (CBN) Statistical Bulletin, the Nigerian Bureau of Statistics Productivity report as well as National Electricity Regulation Commission (NERC) covering 1996-2018. Findings: Findings emanating from the study showed that electricity blackout has negative impact on productivity. The coefficient indicates that a one percent increase in electricity blackout will leads to a 104 percent decrease in productivity. It was equally revealed that electricity price has negative impact on productivity. Electricity generation and population have positive impact on productivity while corruption increases the influence of electricity blackout on productivity by approximately 30 percent. Practical Implication: The study showed that incessant electricity blackout impeded productivity which was further compounded corrupt practices in this critical sector of the economy. The paper recommends a business-friendly environment with an appropriate incentive structure that will stimulate the required development in the power sector for improved productivity.